Some remarks on early medieval churches in Kraków - Pianowski, Zbigniew (Institute of Archaeology Rzeszów University, 2012)
The research of the oldest churches belonging to Kraków agglomeration have been continuously conducted since the second half of the 19th century. In Kraków there have been about thirty churches including the sacral building from the 11th–13th century. Most of them were recognized during the archaeological and architectural research and the others are known from the written sources. The main discoveries include three pre-Romanesque rotundas in the area of a burg city of Kraków, and a St. Benedykt’s rotunda on the Lasota Hill. Further research provide more information regarding the process of using secondary material. The development in the research field makes it possible to change the knowledge about the function of some buildings e.g a semicircular wall from over the Smocza Jama (earlier an apse of the church, now a circular fortifying tower). In literature we can find a number of reconstructions of early medieval sacral buildings with relics in some of them and the remained ones are only theoretical ideas. A few temples are still undiscovered and unrecognized, and some are waiting for its architectural structure to be verified. There could be an attempt of reconstructing a Romanesque Benedictine Abbey in Tyniec and a part of bishop’s residence or cathedral’s capitol in Wawel. The main task for the future is to recognize a settlement background of the churches in Okół and its area.
Uwagi na temat wczesnośredniowiecznych kościołów aglomeracji krakowskiej
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, medieval; Kraków; pre-Romanesque and Romanesque architecture